2010
DOI: 10.1111/j.1742-4658.2010.07643.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor TDP‐43 can affect selected microRNA levels

Abstract: TDP‐43 has recently been described as the major component of the inclusions found in the brain of patients with a variety of neurodegenerative diseases, such as frontotemporal lobar degeneration and amyotrophic lateral sclerosis. TDP‐43 is a ubiquitous protein whose specific functions are probably crucial to establishing its pathogenic role. Apart from its involvement in transcription, splicing and mRNA stability, TDP‐43 has also been described as a Drosha‐associated protein. However, our knowledge of the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
175
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(185 citation statements)
references
References 64 publications
7
175
2
1
Order By: Relevance
“…Unfortunately, we could not detect the reduced expression of let7b, which has recently been reported as the only microRNA that was down-regulated after TDP-43 knockdown in human Hep-3B cells (23). Although this can be attributed to the difference in the expression levels of each miRNA among the cell lines examined, it also remains to be elucidated how TDP-43 affects the biogenesis of let-7b.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Unfortunately, we could not detect the reduced expression of let7b, which has recently been reported as the only microRNA that was down-regulated after TDP-43 knockdown in human Hep-3B cells (23). Although this can be attributed to the difference in the expression levels of each miRNA among the cell lines examined, it also remains to be elucidated how TDP-43 affects the biogenesis of let-7b.…”
Section: Discussioncontrasting
confidence: 47%
“…In contrast, EMSA demonstrated that recTDP-43 bound to pre-miR-574 (Fig. 2D), which is in contrast to a previous report, which demonstrated that premiR-574 did not bind to GST-TDP-43 in vitro (23). To investigate the site within pre-miR-574 that is recognized by TDP-43, first we mutated two nucleotides within the terminal loop to extend the dsRNA region (Fig.…”
Section: Identification Of Mirnas Whose Expression Is Altered By Tdp-43contrasting
confidence: 51%
“…Alternatively, binding to RNA via RRM1 may induce allosteric changes to TDP-43, which in turn regulates interactions with transcriptional complexes. Previous reports suggested that TDP-43 may bind to messenger RNA as well as small microRNAs (25,26,32). Our future work will focus on identification of the RNA molecules that bind to TDP-43 to regulate its transcriptional function.…”
Section: Discussionmentioning
confidence: 99%
“…TDP-43 was initially discovered as a regulator of HIV transcription 33 but since then it was implicated in multiple nuclear and cytoplasmic functions ranging from alternative splicing, 7,34 miRNA biogenesis, 35 mRNA translation, 36 mRNA stability, 30,31 to TDP-43 mRNA levels autoregulation, 16,29 Recently, it was demonstrated its involvement in 3 0 end processing of its own pre-mRNA. High levels of TDP-43 block the recognition of the first PAS present on its transcript by competing with the polyadenylation factor CstF-64 for DSE binding.…”
Section: Discussionmentioning
confidence: 99%